System of Preparation of Future Fitness Coaches' for Health-Improving Activity in the Conditions of Rehabilitation Establishments - Kornosenko, Oksana; Denysovets, Tamara; Danysko, Oksana; Synytsya, Sergiy; Voloshko, Larisa; Zhamardiy, Valeriy; Donchenko, Viktoriia; Shkola, Olena; Prystynskyi, Volodymyr; Otravenko, Olena (International journal of applied exercise physiology, 2020)
To model the structure of the system of future fitness coaches' for health-improving activity in the conditions of rehabilitation establishments. The experimental-experimental work was carried out in three stages: preparatory-organizational, ascertaining-modeling, forming-implementing with the use methods of modelling, system-structural analysis, synthesis, comparison, classification, generalization. As a result of research the structural elements of the system model are distinguished and described: aim of professional training, interaction of lecturers and students, stages of professional training, subject training, educationaltechnical and methodological provision, monitoring of components' formation of future fitness coaches' professional competence, educational environment, and also functional connections between them, integrated components (conceptual, informative, technological, effective). Systematization of structural elements allowed to define the components of fitness coaches' training system of rehabilitation establishments: conceptual, informative, technological, effective, that will assist the enhance of educational process' quality.